Effect of annealing temperature and laser pulse energy on the optical properties of CuO films prepared by pulsed laser deposition - Aadim, Kadhim A. (Iraqi Journal of Physics, 2019)
In this work; copper oxide films (CuO) were fabricated by PLD. The films were analyzed by UV-VIS absorption spectra and their thickness by using profilometer. Pulsed Nd:YAG laser was used for prepared CuO thin films under O2 gas environment with varying both pulse energy and annealing temperature. The optical properties of   as-grown film such as optical transmittance spectrum, refractive index and energy gap has been measured experimentally and the effects of laser pulse energy  and annealing temperature on it were studied. An inverse relationship between energy gap and both annealing temperature and pulse energy was observed.